PERAN ORANG TUA TERHADAP PERTUMBUHAN IMAN ANAK DI GEREJA KELUARGA TABGHA ALMA JAYA MALAYSIA - Djaafar, Andre; Setiawan, Eko Agus; Siringoringo, Marito; Purba, Gomgom (JURNAL TABGHA, 2024)
Parents are men and women who are bound by marriage and are ready to assume responsibility as the father and mother of the children they give birth to. Parents are two different individuals entering life together by bringing views, daily habits. The writer of Proverbs also emphasized to parents to use the "rod of discipline" with their children in guiding them to have faith in God. He who does not use a stick hates his children, but he who loves his children chastens them in time (Proverbs 13:24). It is also said that there is a time when children are so easily guided to know God. This time should be used by parents as soon as possible. “Behold your child as long as there is hope, but do not desire his death (Proverbs 19:18). The results of this research can be used as a theoretical basis regarding the role of parents in the growth of children's faith. The results of this research can be studied theoretically and academically by Theological Colleges and Christian researchers. In writing this thesis the researcher used qualitative research methods. And the author uses basic theories from various sources, namely: books and the Bible. From this research, it was found that parents have played a role in the growth of children's faith so that the results can be that children who experience growth in faith experience spiritual formation and the children provide themselves to be involved in service at the local church.